2018
DOI: 10.1371/journal.pone.0193644
|View full text |Cite
|
Sign up to set email alerts
|

KRAS mutant allele-specific expression knockdown in pancreatic cancer model with systemically delivered bi-shRNA KRAS lipoplex

Abstract: The KRAS oncogene, present in over 90% of pancreatic ductal adenocarcinomas, is most frequently the result of one of three gain-of-function substitution mutations of codon 12 glycine. Thus far, RAS mutations have been clinically refractory to both direct and selective inhibition by systemic therapeutics. This report presents the results of pre-clinical assessment of a lipoplex comprising a plasmid-encoded, modular bi-functional shRNA (bi-shRNA), which executes selective and multi-mutant allelic KRASG12mut gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 47 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Several alternative targeted delivery strategies have been explored in PDAC over the last decades. These strategies employ-amongst others-liposomes [23][24][25][26], poly(lactic-co-glycolic acid) (PLGA)-based polymeric nanoparticles [27][28][29], solid lipid nanoparticles [30][31][32], and mesoporous silica nanoparticles (MSNs) of which especially the use of MSNs seems an attractive approach. MSNs are nanoscale silica-based particles with a porous structure as implied by their name.…”
Section: Targeted Deliverymentioning
confidence: 99%
“…Several alternative targeted delivery strategies have been explored in PDAC over the last decades. These strategies employ-amongst others-liposomes [23][24][25][26], poly(lactic-co-glycolic acid) (PLGA)-based polymeric nanoparticles [27][28][29], solid lipid nanoparticles [30][31][32], and mesoporous silica nanoparticles (MSNs) of which especially the use of MSNs seems an attractive approach. MSNs are nanoscale silica-based particles with a porous structure as implied by their name.…”
Section: Targeted Deliverymentioning
confidence: 99%
“…Rao et al have demonstrated KRAS down-regulation by a lipoplex encoding a short hairpin RNA via systemic injection in a pancreatic cancer model [ 51 ]. The lipoplex contained a plasmid encoding a short hairpin RNA that executes selective silencing of the mutated KRAS gene with tumor cell entry facilitated by facilitated by fusogenic liposomes.…”
Section: Rnai Delivery Strategies For Pancreatic Cancer Therapymentioning
confidence: 99%
“…For example, dioleoyl phosphatidylethanolamine (DOPE) increases the endosomal escape ability of DNA after endocytosis of cationic liposome/DNA complex 23,24. In a pancreatic cancer model, recent studies reported the use of a liposome complex to deliver shRNAs or anti-miRNA oligonucleotides for therapeutic purposes 25,26. Liposomes are also used for efficient antigen delivery and enhanced immune response in developing vaccines 2729.…”
Section: Introductionmentioning
confidence: 99%